Assessment of wellbeing of undergraduate students using PERMA+ model: A brief report from Western Maharashtra, India - Mihir R. Vakhariya; Supriya S. Patil (Journal of Education and Health Promotion)
In the realm of medical education, the wellbeing of students is a critical but often overlooked aspect. To assess the wellbeing of undergraduate students through the application of PERMA+ model while also investigating the influence of sociodemographic factors on their wellbeing. This cross-sectional study, approved by the Institutional Ethics Committee, involved 364 undergraduate medical students at Krishna Institute of Medical Sciences, Karad, Maharashtra, India. Participants provided informed consent and completed a validated questionnaire. Statistical analyses, including Chi-square test, unpaired t-test, ANOVA, and Pearson correlation, were conducted using IBM SPSS version 20. P < 0.05 was considered statistically significant. Poor wellbeing was reported by 45 (12.4%), average wellbeing by 174 (47.8%), and good wellbeing by 145 (39.8%) among participants, resulting in an overall mean score of 6.65 ± 1.39. Notably, males exhibited higher overall wellbeing than females. However, there was a discernible impact of the professional year, with fourth year displaying the highest mean score at 6.95 ± 1.39. Health scores predominantly fell in medium category, with a mean of 6.43 ± 2.03. In addition, 64 (17.6%) reported high negative emotions, while 71 (19.5%) experienced elevated loneliness. Correlation analyses revealed a significant positive association between negative emotions and loneliness (r = 0.340). The findings reveal variations in wellbeing levels, notably males exhibited higher overall wellbeing, and the fourth professional year stands out with the highest mean score. The study highlights the interconnectedness of emotional experiences. The study emphasizes the multifaceted nature of factors influencing wellbeing, calling for targeted interventions.